TFE3-Mediated Autophagy is Involved in Dopaminergic Neurodegeneration in Parkinson’s Disease - He, Xin; Xie, Yue; Zheng, Qiongping; Zhang, Zeyu; Ma, Shanshan; Li, Junyu; Li, Mingtao; Huang, Qiaoying (Frontiers in Cell and Developmental Biology, 2021)
Impairment of autophagy has been strongly implicated in the progressive loss of nigral dopaminergic neurons in Parkinson’s disease (PD). Transcription factor E3 (TFE3), an MiTF/TFE family transcription factor, has been identified as a master regulator of the genes that are associated with lysosomal biogenesis and autophagy. However, whether TFE3 is involved in parkinsonian neurodegeneration remains to be determined. In this study, we found decreased TFE3 expression in the nuclei of the dopaminergic neurons of postmortem human PD brains. Next, we demonstrated that TFE3 knockdown led to autophagy dysfunction and neurodegeneration of dopaminergic neurons in mice, implying that reduction of nuclear TFE3 may contribute to autophagy dysfunction-mediated cell death in PD. Further, we showed that enhancement of autophagy by TFE3 overexpression dramatically reversed autophagy downregulation and dopaminergic neurons loss in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model of PD. Taken together, these findings demonstrate that TFE3 plays an essential role in maintaining autophagy and the survival of dopaminergic neurons, suggesting TFE3 activation may serve as a promising strategy for PD therapy.